Program Pengembangan Kemampuan Kognitif Anak Usia Dini Melalui Kegiatan Meronce Menggunakan Bahan Alam - Kasiyati, Kasiyati (Program Studi S1 PG-PAUD, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Satya Wacana, 2023)
The purpose of this study is to ascertain whether children's cognitive capacities may be enhanced by natural material merging activities. There were twenty-five kids in Group B2 Kartika PGRI Tambakmulyo Kindergarten who served as the research subjects. Cycle I showed the start of the research implementation, which concluded in Cycle II. Every cycle involves the following four steps: planning, implementation, observation, and reflection. Documentation and observation sheets were employed as data gathering strategies. This study employs a quantitative, descriptive data analysis methodology. Preliminary assessments prior to the intervention revealed that 20% of the participants had complete cognitive competence. Cycle I showed an increase in the use of natural material-assisted merging operations to 56% of the participants, and Cycle II has reached the success indicator of 88%. These findings suggest that the raffling exercise, when aided by natural materials, can enhance the cognitive capacities of the kids in Group B. Kindergarten Kartika PGRI Tambakmulyo.